The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of 6th Eurasphalt &Amp; Eurobitume Congress 2016
DOI: 10.14311/ee.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

Cold recycling process using renewable resources: contribution of rheological and chromatographic methods for rejuvenating mechanism and duration assessment

Abstract: Recycling end-of-life road products can be performed in various ways, involving a combination of sustainable techniques. A first level in sustainability is reached by the use of a bitumen emulsion, which enables processing at moderate temperatures. This technique is already commonly used, according to specific guidelines. Further improvement is achieved if the emulsion contains a rejuvenating agent manufactured from renewable resources. In this context, the key issue in laboratory study is to find a proper way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…However, since then, different research studies have reported the limitations of these criteria to avoid the poor field performance of some bitumens [54] or validate the enhanced performance of other bitumens (e.g., polymer-modified bitumens) [55]. Nevertheless, other studies have proposed different rheological-based indicators, which can be expected to be included in the next bitumen specifications, such as in the upcoming revisions of the European standards [56]. In addition, bitumens incorporating biomaterials are non-conventional bituminous binders, and the proposed rheological indicators may not apply to them.…”
Section: Lve Rheological-based Performance Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since then, different research studies have reported the limitations of these criteria to avoid the poor field performance of some bitumens [54] or validate the enhanced performance of other bitumens (e.g., polymer-modified bitumens) [55]. Nevertheless, other studies have proposed different rheological-based indicators, which can be expected to be included in the next bitumen specifications, such as in the upcoming revisions of the European standards [56]. In addition, bitumens incorporating biomaterials are non-conventional bituminous binders, and the proposed rheological indicators may not apply to them.…”
Section: Lve Rheological-based Performance Indicatorsmentioning
confidence: 99%
“…The other indicators correspond to two stiffness levels (|G*| = 50 kPa and |G*| = 5 MPa) that have been intensively discussed regarding their inclusion in the revisions of the European standards for bituminous binders, despite them requiring for now only the reporting of test values. The temperature at the highest stiffness (5 MPa) is aimed at giving an indication of fatigue cracking performance so that the lower the temperature is, the better the expected performance [56]. In opposition, the higher the temperature for the lower stiffness level (50 kPa), the better the expected performance for rutting resistance [56].…”
Section: Lve Rheological-based Performance Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation